(untitled) (Iraqi Journal of Science, 2022)
The present study was aimed to screen the ability of local isolates of Bacillus spp. (56 isolates) for nattokinase production using solid state fermentation, then optimize the nutritional conditions for enzyme production. The isolates were subjected to the primary and secondary screening process to select the Bacillus isolate which give the highest production of enzyme. It was found that Bacillus sp. B24 had the highest productivity of the enzyme (25.58U/mg protein). The optimum conditions for nattokinase production were performed by the solid state fermentation and found that the wheat bran was the best medium at initial moisture ratio 1.0:1.0 (w/v) using distilled water as moisturizing solution with initial pH of 7.0 after inoculation with 5×107 cell/ml for 72 hrs, the enzyme specific activity was 38.65U/mg protein.